(3SDGd hLhGH Yf LeGYI ef GdbUGU jLdShf aj GdeSLO hjLJeY Ydjge GdfSGAs
(3ChdgG (B:s
(3SDGd QaY ddTjN CHj YHO Gddg eMeO Hf eMeO Hf YdGA GdOjf GdHNGQi s
(3BNQgG (B:s
(3aEf dge ai Pdc GdKfGA GdLejd ai GdOfjG hGdKhGH GdLRjd ai GdYbHi hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGef hGdYTQhfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP GdOcJhQ ESMGb ehSi GdMSjfi GdNGUI s
Keywords: (3Gdabg GdTGaYjs